South Asian Nuclear Security or Deterrence: An Analysis - Muhammad Saleem Mazhar; Naheed S. Goraya (Journal of Political Studies, 2016)
Nuclear deterrence has by and large been unrelenting in South Asia since 1971 however a twist of events may abruptly alter this state to a degree that could prompt the decision-makers to go for rapid and illogical decisions. This paper studies the deterrence theory, nuclear terrorism, the prospects of Limited War vis-à-vis repercussions for South Asia and gives recommendations how deterrence be stabilized and peace preserved in South Asia